1995
DOI: 10.1021/jm00013a023
|View full text |Cite
|
Sign up to set email alerts
|

(Piperidinylalkoxy)chromones: Novel Antihistamines with Additional Antagonistic Activity against Leukotriene D4

Abstract: A series of novel chromone derivatives, in which the chromone moiety is connected to a (diphenylmethylene)-, (diphenylmethyl)-, or (diphenylmethoxy)piperidine via an alkyloxy spacer, were synthesized as antiallergic and antiasthmatic agents. In addition to their potent antihistaminic activity, the compounds also inhibit contraction in guinea pig ileum induced by leukotriene D4. When analyzed by radioligand binding assays in guinea pig lung membranes, one of the compounds, 7-[[3-[4-(diphenylmethylene)piperidin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
0
26
0
1
Order By: Relevance
“…The results of this study indicate that aloesin is a strong inhibitor of LTB 4 release, suggesting that aloesin may reduce the accumulation of neutrophils and leukocytes within the mucosa. Zhang et al (1995) reported that the chromone moiety effectively inhibits a LTD4-induced increase in vascular permeability. Huang et al (1991) found that the chromone moiety in the benzopyran-4-one ring led to a significant increase in leukotriene D4 receptor binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicate that aloesin is a strong inhibitor of LTB 4 release, suggesting that aloesin may reduce the accumulation of neutrophils and leukocytes within the mucosa. Zhang et al (1995) reported that the chromone moiety effectively inhibits a LTD4-induced increase in vascular permeability. Huang et al (1991) found that the chromone moiety in the benzopyran-4-one ring led to a significant increase in leukotriene D4 receptor binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…2 Fig. 2)-4-(diphenylmethoxy)piperidine [30] and 1,1-difluoro-2-phenylethane [31] were prepared as described previously.…”
Section: Synthesis Of Ebastine and Terfenadone Derivativesmentioning
confidence: 99%
“…Como exemplos de agentes terapêuticos broncodilatadores podemos citar: os agonistas β 2 adrenérgicos 44 , anticolinérgicos 45 , metilxantinas 46 e moduladores de canais de potássio 41 . Por sua vez, os corticosteróides 47 , antagonistas de bradicinina 48 , anti-histamínicos 49 , inibidores de fosfolipase A 2 (PLA 2 -i) 50 , inibidores de tromboxana sintase (TXSi) 51 , antagonistas de receptores de TXA 2 (TPant) 52 , antagonistas de receptores de PAF (PAFant) 53 , inibidores de LTA 4 -hidrolase 54 , inibidores de 5-lipoxigenase (5-LO-i) 55 , são exemplos de agentes antiinflamatórios, úteis para o tratamento do processo asmático.…”
Section: Terapia Antiasmática Clássicaunclassified